2023
DOI: 10.3389/fitd.2023.1091545
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for arboviruses and leptospirosis among non-malarial acute febrile illness outpatients in areas affected by Cyclones Idai and Kenneth in Mozambique

Abstract: The floods associated with the landfall of cyclones Idai and Kenneth in Mozambique between March and April 2019 had a major impact on the country’s public health and placed the affected population at risk for vector- and rodent-borne diseases. Aiming to improve the diagnostic capacity, yield information to guide public health responses, and assess potential short-term effects of cyclones Idai and Kenneth on arboviruses (dengue, Zika, and chikungunya) and leptospirosis, a clinical and laboratory surveillance fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…31 Its geographical location predisposes the country to extreme weather events such as heavy floods, cyclones, storms, floods, and drought, which in turn exacerbate the burden of climate-sensitive diseases due to contamination of water and food. 19 Maputo City, the country's capital, has approximately 1.12 million inhabitants with half of the population residing in unplanned settlements, leading to high population density and poor access to basic safe drinking water and sewage drainage. 32 We conducted a cross-sectional study between March 2020 and October 2021 in Maputo Central Hospital, the largest referral hospital in the country, which also serves as a teaching hospital for undergraduate students at Eduardo Mondlane University, Faculty of Medicine and for training of specialists and other health professionals such as nurses and physician technicians.…”
Section: Study Setting Design and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…31 Its geographical location predisposes the country to extreme weather events such as heavy floods, cyclones, storms, floods, and drought, which in turn exacerbate the burden of climate-sensitive diseases due to contamination of water and food. 19 Maputo City, the country's capital, has approximately 1.12 million inhabitants with half of the population residing in unplanned settlements, leading to high population density and poor access to basic safe drinking water and sewage drainage. 32 We conducted a cross-sectional study between March 2020 and October 2021 in Maputo Central Hospital, the largest referral hospital in the country, which also serves as a teaching hospital for undergraduate students at Eduardo Mondlane University, Faculty of Medicine and for training of specialists and other health professionals such as nurses and physician technicians.…”
Section: Study Setting Design and Methodsmentioning
confidence: 99%
“…7 The seroprevalence of Leptospira found in our study is higher than that reported from other studies done in Mozambique among febrile patients. 19,35 In these studies, the seroprevalence of Leptospira varied from 1.3% using the MAT assay to between 11.5% and 34.1% using ELISA IgM. We did not test for IgM antibodies due to financial limitations.…”
Section: Serologymentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission can occur when infected urine is in contact with skin cuts and abrasions and inhalation of contaminated aerosols [11,12]. Studies that were conducted in Mozambique by Ribeiro et al (2017) and Mugabe et al (2023) have shown leptospirosis among non-malaria febrile patients in the southern, and central regions of the country [13,14]. According to Comia et al pathogenic species of Leptospira was identified in rodents using molecular methods in the northern Nampula province.…”
Section: Introductionmentioning
confidence: 99%